2018
DOI: 10.1371/journal.pone.0194061
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the utilization of postpartum family visits: Evidence from rural areas of Eastern China

Abstract: BackgroundPostpartum Family Visits (PFVs) have been advocated as a way to improve health outcomes for puerperal women and their newborns. This study aimed to identify individual factors associated with the utilization of PFVs in rural Jiangsu Province, China.MethodsWe employed responses of the household survey in Jiangsu province, part of the National Health Service Survey (NHSS), a nationally representative survey in China. The data analysis framework was designed based on Andersen’s behavioral model. The out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 29 publications
3
18
0
1
Order By: Relevance
“…This may be explained by the role of knowledge in increasing awareness of basic health services and health risks, leading to improved health-seeking behavior. This finding is in agreement with results from various developing countries 15,16,20,51,52 and from other studies in rural Ethiopia. 14,48,53…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This may be explained by the role of knowledge in increasing awareness of basic health services and health risks, leading to improved health-seeking behavior. This finding is in agreement with results from various developing countries 15,16,20,51,52 and from other studies in rural Ethiopia. 14,48,53…”
Section: Discussionsupporting
confidence: 93%
“…Our study found the odds of non-utilization of PNC services were higher among women who had never visited health facilities for ANC services than among those who had, corroborating the findings of other studies. 4,7,16,20,34 Similarly, recent demographic health surveys across African countries indicate that rural postnatal residents who were ANC non-users had higher odds of not receiving postnatal services. 5 Furthermore, our study revealed that women who had experienced postnatal complications after their last birth were much more likely to visit a reproductive health facility for PNC services than those who had not encountered any complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The postpartum care visit is an important opportunity to follow up women at increased risk for certain conditions such as anemia as well as impaired physical health and emotional problems. However, compliance with postpartum healthcare recommendation is not consistent and healthcare services utilization can be absent in 10-40% of puerperal women, depending on the specific area and population [10][11][12]. Thus, it is important to identify populations at increased risk for postpartum anemia and low compliance with medical surveillance in order to change policies that will assist in decreasing anemia prevalence in Israel and improve patients' medical care.…”
Section: Introductionmentioning
confidence: 99%